DEVELOPING ENGLISH LANGUAGE LEARNING MATERIALS (ELLMs) FOR THE 1ST YEAR ECONOMIC STUDENTS AT DHARMA ANDALAS UNIVERSITY - Yalmiadi, Yalmiadi - (TELL - US JOURNAL, 2019)
AbstractThe development of the ELLMs arouse from the ultimate current trend towards incessantly using the inauthentic, generic and commercial ELT textbooks as the primary teaching and learning resources for the Dharma Andalas University’s Economic students. The effects of using the inauthentic materials fail to represent the knowledge and skills of English used in real world “language” settings. The objective of this study was, therefore, to research the students’ ELT materials as well as develop the authentic materials as a response to meeting/fulfilling the student’s needs of learning English. The method used was the Four D instructional model which underlined the four cyclical stages of Define, Design, Develop and Disseminate. The data were qualitatively and quantitatively processed. The research findings indicated that the developed instructional volume of the ELLMs for the 1st Year Dharma Andalas University’s Economic students were valid, effective and practical. In conclusion, the valid, effective and practical instructional volume of the ELLMs best described the students English needs, represented the knowledge and skills of English used in real world setting and significantly augmented the students’ vocabulary knowledge, productive and receptive skills. Keywords: developing, ELLMs, economic student, Dharma Andalas University